The miracles and "translatio" of Saint James : Books Two and Three of the Liber Sancti Jacobi - Coffey, Thomas F.; Coffey, Thomas F.; Dunn, Maryjane; Dunn, Maryjane (Medieval and Renaissance Texts., 2018)
"A translation of the 'Miracles' and 'Translatio' of Saint James from Books Two and Three of the Liber Sancti Jacobi, with Introduction, Commentaries and Notes, documents related to the pilgrimage route to Santiago de Compostela"--Provided by publisher.